First join the log4 on the left:
log4( x*(x-3) = log4(-7x+21)
Then x = -7, works: -7*(-10)=70 = -7*(-7)+21
x=-3, 18 = 42, does not work
x=3 0=0 works,
However, when one puts x = -7 in the *original* exression, log4(-7) or log4(-10) do not exist (you know why?). So x= -7 is extraneous.
Now x=3 gives log4(0) on the left and right, which does not exist.
So, C is the answer, both are extraneous. Seem to work but indeed don't work in the *original* equation
John's share of the money is 12.75.
38.25 ÷ 4.5 = 8.5
8.5 · 1.5 = 12.75
Step-by-step explanation:
10 is the value of A ......
Answer:
23.6666666667
Step-by-step explanation: